A Low-Cost Layered Double Hydroxide (LDH) Based Amperometric Sensor for the Detection of Isoproturon in Water Using Carbon Paste Modified Electrode. (21st August 2020) - Tcheumi, Herve Leclerc; Kameni Wendji, Aude Peggy; Tonle, Ignas Kenfack; Ngameni, Emmanuel
Abstract : In this work, a Layered Double Hydroxide (NiAl-LDH) was obtained by coprecipitation method and used to elaborate an electrochemical sensor for the determination of isoproturon, which is a hazardous pollutant, widely used in agriculture, and its residue is distributed into aqueous environment through run-off and leaching from the soil. Various physicochemical techniques such as FT-IR spectroscopy, X-ray diffraction, and thermal analysis were used to characterize this material. The anionic exchange capacity of NiAl-LDH on carbon paste modified electrode was investigated toward [Fe(CN)6 ] 3- using cyclic voltammetry. Used as electrode modifier of carbon paste electrode for isoproturon detection, a remarkable increase in isoproturon signal on modified carbon paste electrode by LDH was observed. The peak current obtained after 3 min of preconcentration in 25 μ M ISO on NiAl-LDH/CPE was 2.6 times higher than that exhibited by the same analyte on the unmodified CPE, thereby opening the way to the development of a sensitive method for the detection of ISO. Other parameters that can affect the stripping response (preconcentration time, pH of detection medium, and LDH loading within the paste) were investigated to optimize the proposed sensor. After optimization, a linear calibration curve was obtained in the concentration range from 2 × 10 −8 to 1.8 × 10 −7 M, leading to a detection limit of 1 × 10 −9 M (S/N = 3). The relative standard deviation for 5 identical measurements was 2.7%. The interfering effect of some compounds and ions was examined on the stripping response of ISO. The applicability of the method was verified by the determination of ISO in spiked water sample.